Hospital and Domiciliary Services Outcome: A Cross-Sectional Study on Married Women of Peshawar Khyber Pakhtunkhwa - Bushra Iftikhar; Kashif KhalilurRehman; Laiba Majid; furqan UlHaq; Sara Nisar; Syeda TayyabaBukhari; Noman salih; Syed SulimanShah; Israr Khan; Azhar Hussain (ziauddin University, 2024)
Background: Antenatal care and effective services are the hallmarks of effective pregnancy outcome. Thus, practices by community care providers throughout labor and childbirth might affect health outcomes of newborns. There is a need for proper antenatal checkups in hospital and domiciliary care by community health workers and importance of antenatal care on pregnancy outcomes. Since, every woman has a right to safe delivery that must include proper labor management protocols. Therefore, the purpose of this study was to compare and assess the antenatal care of hospital based and domiciliary services on the outcome of delivery. Methods: This cross-sectional study was conducted from November 2018-April 2019. A sample size of about 300 married females was selected from different towns of Peshawar through non-probability convenient sampling technique. Data was collected using semi structured questionnaire after taking informed consent from the women. Data were analyzed by using SPSS. Chi square test was applied for associations between hospital and domiciliary services and antenatal outcomes in both setups. p-value < 0.05 was considered signiﬁcant. Results: The comparison of hospital and domiciliary services on the outcome of newborn and mother, showed better services of hospital. Domiciliary care services showed increased number of complications in females during delivery (p-value<0.05) and in newborn (p-value< 0.05) compared to hospital services. Conclusion: Hospital services provide antenatal care by trained person majority of deliveries were normal, while in cases of domiciliary-based services majority faced complications during pregnancy and delivery. Awareness of community is important step to improve mother and child health. Keywords: Antenatal Care; Domiciliary Service; Hospital Services.